The potential of melatonin and its crosstalk with other hormones in the fight against stress - Xu, Lina; Zhu, Yafei; Wang, Yakun; Zhang, Luyan; Li, Lijie; Looi, Ley Juen; Zhang, Zhiyong (Frontiers Media, 2024)
Climate change not only leads to high temperatures, droughts, floods, storms and declining soil quality, but it also affects the spread and mutation of pests and diseases, which directly influences plant growth and constitutes a new challenge to food security. Numerous hormones like auxin, ethylene and melatonin, regulate plant growth and development as well as their resistance to environmental stresses. To mitigate the impact of diverse biotic and abiotic stressors on crops, single or multiple phytohormones in combination have been applied. Melatonin is a multifunctional signaling molecule engaged in the development and stress response of plants. In the current review, we discuss the synthesis and action of melatonin, as well as its utilization for plant resistance to different stresses from the perspective of practical application. Simultaneously, we elucidate the regulatory effects and complex mechanisms of melatonin and other plant hormones on the growth of plants, explore the practical applications of melatonin in combination with other phytohormones in crops. This will aid in the planning of management strategies to protect plants from damage caused by environmental stress.